2008
DOI: 10.1073/pnas.0805212105
|View full text |Cite
|
Sign up to set email alerts
|

Locations of the β1 transmembrane helices in the BK potassium channel

Abstract: BK channels are composed of ␣-subunits, which form a voltageand Ca 2؉ -gated potassium channel, and of modulatory ␤-subunits. The ␤1-subunit is expressed in smooth muscle, where it renders the BK channel sensitive to [Ca 2؉ ]i in a voltage range near the smoothmuscle resting potential and slows activation and deactivation. BK channel acts thereby as a damped feedback regulator of voltagedependent Ca 2؉ channels and of smooth muscle tone. We explored the contacts between ␣ and ␤1 by determining the extent of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
89
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(96 citation statements)
references
References 39 publications
7
89
0
Order By: Relevance
“…Disulfide crosslinking has been widely used to determine quaternary structures of proteins and to determine regions that move during changes in functional states (24). Using our variation of this approach (25,26), we substituted Cys, one at a time, in the first four positions just flanking the extracellular ends of Q1 S1-S6 and just flanking the extracellular end of the E1-TM. We expressed 80 distinct pairs of Cys-substituted Q1 and Cys-substituted E1 in CHO cells and determined the extents of spontaneous disulfide bond formation between Q1 and E1 in channels expressed on the cell surface.…”
mentioning
confidence: 99%
“…Disulfide crosslinking has been widely used to determine quaternary structures of proteins and to determine regions that move during changes in functional states (24). Using our variation of this approach (25,26), we substituted Cys, one at a time, in the first four positions just flanking the extracellular ends of Q1 S1-S6 and just flanking the extracellular end of the E1-TM. We expressed 80 distinct pairs of Cys-substituted Q1 and Cys-substituted E1 in CHO cells and determined the extents of spontaneous disulfide bond formation between Q1 and E1 in channels expressed on the cell surface.…”
mentioning
confidence: 99%
“…Direct structural interaction between the β1 subunit and the BK voltage-sensing domain is supported by functional and biochemical analysis, which has demonstrated a key role for the S0 transmembrane helix and suggested that there are direct molecular contacts between S0 and the second transmembrane segment (TM2) of the β1 subunit, and between S1 and S2 and the first transmembrane segment (TM1) (Wallner et al, 1996;Morrow et al, 2006;Liu et al, 2008). Similarly, gating effects of the neuronal β4 subunit could be explained by stabilization of the BK channel voltage sensor in the activated state, in combination with relative stabilization of the pore in the closed state in the absence of voltage-sensor activation, giving rise to a gating phenotype in which the voltage-dependent activation is shift toward more positive voltages at low [Ca 2+ ] and more negative voltages at higher [Ca 2+ ] in channels comprised of alpha + β4 subunits (Wang et al, 2006;Wu et al, 2009).…”
Section: +mentioning
confidence: 91%
“…The S1-S6 segments are analogous to the S1-S6 of the other Kv channels; the S5-S6 segments line the pore, and the S1-S4 segments contribute to "sensing" the transmembrane voltage, by way of a series of charged residues in the S4 region. The additional and relatively unique S0 region gives the BK channel an extracellular N-terminus, and forms a functionally important interaction with the β1 subunit (Wallner et al, 1996;Meera et al, 1997;Morrow et al, 2006;Liu et al, 2008). The S0 segment also forms an integral part of the BK channel voltage-sensor domain (Koval et al, 2007;Pantazis et al, 2010).…”
Section: Basic Architecture and Subunit Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…The auxiliary β1 subunit of BK channels alters the voltage-dependence by interacting with S0, S1 and S2 in the periphery of the VSD [210,211].…”
Section: Auxiliary Subunitsmentioning
confidence: 99%